IoT-Based Monitoring System for Temperature and pH Control in Cocoa Fermentation - Sabila, Liya Yusrina; Dwiyono, Linggar Rahmat; Hakim, Agus Rahman; Karuana, Abi Nazli; Hakika, Dhias Cahya (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2025)
Cocoa fermentation plays a crucial role in cocoa bean production, as it directly influences the taste, aroma, and texture of the final product. Temperature and pH significantly impact microbial activity during fermentation, making their control essential for achieving optimal and consistent results. A promising solution is the implementation of an IoT-based system for temperature regulation and pH monitoring, allowing for real-time data tracking throughout the fermentation process. This study developed a cocoa fermentation box integrated with an IoT system, utilizing a DHT22 temperature sensor and a 4502C pH sensor for precise monitoring. The system enables real-time data access and remote control, improving efficiency and quality while transforming conventional manual observation methods into a standardized, data-driven approach. IoT technology facilitates rapid condition adjustments and predictive analysis, minimizing human error and reducing the risk of fermentation inconsistencies. The experimental results demonstrated high sensor accuracy, with the IoT system successfully enhancing efficiency, control, and cocoa bean quality. In the 1 kg cocoa test, temperatures ranged from 28℃ to 35℃, with pH values between 4.0 and 5.3. In the 10 kg experiment, temperatures on the second day ranged from 28℃ to 33℃ with pH values between 4.3 and 5.9, while on the third day, temperatures ranged from 28℃ to 32℃, with pH values stabilizing between 4.0 and 5.3.